Investigation of the Growth of Broiler Chickens Fed with Azolla Mixed Feed: A Sustainable Protein Source for Rural Farming (Journal of the Bangladesh Agricultural University, 2026)
The inclusion of Azolla in broiler feed is becoming popular in rural areas to produce meat chicken at a reasonable cost in a sustainable manner. The present study investigated the effects of Azolla inclusion in feeding of broiler chickens under rural farming conditions. For this experiment, conventional and Azolla mixed (10% Azolla with 90% conventional) feedings were carried out with chicks (n=90) and 45 chicks in each feeding group with three replicates and collected data for six weeks. Thirty non-trained panelists carried out the sensory analysis of cooked meat. The data were statistically analyzed. The results showed that mean weight gain, FCR, organs weight except for head as well as sensory parameters of cooked meat were not significantly different while the weight of head was significantly different (p